Penerapan Aplikasi Canva Sebagai Media Pembelajaran Teks Diskusi Kelas IX SMP Negeri 36 Semarang - Brillian Syaifullah; Khusnul Fadlyanim; Fahrudin Bustomi; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Amilia Buana Dewi Islamy; Herry Erwanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education is a process carried out to change the mindset and behavior of humans into individuals who have good character, insight, and quality in order to become individuals with dignity. The development of an increasingly advanced era demands that the learning process in schools use technology as a means of supporting learning activities, for example in the use of learning media. One of the learning media that utilizes current technological developments is Canva. This article aims to describe the application of Canva media as a learning medium to examine the structure and language of discussion texts in class IX H Junior High School 36 Semarang. The benefit of applying Canva as a learning medium for studying discussion text material is that students are more interested and find it easier to understand how to study the structure and language rules of discussion texts.